ASESMEN PERKEMBANGAN MOTORIK KASAR ANAK USIA 4-5 TAHUN - Maulidiyah, Eka Cahya (Martabat: Jurnal Perempuan dan Anak, 2017)
Assessment gross motor development of children aged 4-5 years aims todetermine the development of children aged 4-5 years according to the level ofgross motor development. Knowing the delay and the possibility of its specialneeds in children, and making plan for gross motor development programchildren from the assessment that has been done. The assessment was conductedin early childhood institutions in Jl Permata Bunda. Benda Jaya RT / RW007/012 Duren Sawit. The subjects included 20 students. Students hadan age range of 4-5 years with varygross motor skills. Data were processedusing Rio Anates to see the number of per-individual scores, the average score,reliability, as well as the significance or correlation score items with a total score.The scale used is the scale rating. Through the scale rating raw data obtainedin the form of numbers and then interpreted in a qualitative sense. The datais identified to produce the screening, which is subsequently used as the basisto create grouping, a mapping, and planning a learning program that fits theneeds of children in whole or individually.Keywords: Asesmen, Motorik, Motorik Kasar, Anak, Anak Usia Dini